Impact of ASHRAE standard 189.1-2009 on building energy efficiency and performance - Blush, Aaron (Kansas State University, 2010)
The purpose of this report is to provide an introduction to the new ASHRAE Standard 189.1-2009, Standard for the Design of High-Performance Green Buildings. The report will include an overview of the standard to detail what the purpose, scope and requirements for high-performance buildings will be. The entire standard will be overviewed, but the focus of this paper is in the areas of energy efficiency and building performance. Next, the report will examine further impacts that the standard will have on the building design and construction industry. Chapter 3 includes the impact on other standards, specification writing and coordination of the design and construction teams. A case study of an office building is performed to compare a baseline building meeting ASHRAE Standard 90.1 to a building meeting the minimum standards of ASHRAE Standard 189.1. The case study compares the total annual energy use of the two projects to determine an expected energy savings. Based on this information, recommendations about the new standard will be discussed. Universities and government entities should require ASHRAE Standard 189.1 for new construction projects, to show willingness to provide sustainability in buildings. Finally, conclusions about how the standard will change and impact industry will be addressed. These conclusions will include issues with adopting ASHRAE Standard 189.1 as code as well as discussion on the LEED rating system.
Keywords: High-performance buildings; Green building; ASHRAE Standard 189.1; Building energy efficiency; Architecture (0729); Engineering, General (0537)